Refugee Admissions and Public Safety: Are Refugee Settlement Areas More Prone to Crime? - Catalina Amuedo-Dorantes; Cynthia Bansak; Susan Pozo (Institute of Labor Economics (IZA), 2018)
According to United Nations High Commissioner for Refugees, the number of refugees worldwide rose to 21.3 million in 2015. Yet, resistance to the welcoming of refugees appears to have grown. The possibility that refugees may commit acts of terrorism or engage in criminal behavior has served as fuel for the Trump Administration's position in 2017. Is there any basis for these fears? We exploit the variation in the geographic and temporal distribution of refugees across U.S. counties to ascertain if there is a link between refugee settlements and local crime rates or terrorist events in the United States. We fail to find any statistically significant evidence of such a connection.
Keywords: F22; J61; J68; 330; refugees; crime; United States; terrorism